Surfactant assisted CaO-based sorbent synthesis and their application to high-temperature CO2 capture - Jamrunroj, Panupong; Wongsakulphasatch, Suwimol; Maneedaeng, Atthaphon; Cheng, C. K.; Assabumrungrat, Suttichai (Elsevier Ltd, 2019)
The concern of carbon dioxide (CO2) emissions, a main contribution of greenhouse gases, has been emerged as an important issue for environmental impact. Adsorption of CO2 by porous solid materials is proven to be one of efficient techniques for CO2 capture technologies. In the present work, attempted has been made to improve property of porous solid materials, CaO-based sorbent, applied for high-temperature CO2 capture. CaCO3 and CaO-based alumina was synthesized using precipitation technique with the addition of sulfonic single chain (SDS) and gemini (12-carbon hydrophobic chains and 3-carbon alkyl spacer, 12-3-12) surfactants for controlling/modifying physical properties. Our studies showed that the addition of anionic surfactants affected phase formation and polymorph of CaCO3, where stronger effect was observed with gemini surfactant. The synthetic CaCO3 was derived to form CaO and applied for capturing CO2 at 600 °C, 15% v/v CO2 (N2 balanced). The results showed that CaO synthesized with adding gemini surfactant offered higher CO2 sorption capacity than single chain surfactant. By incorporating calcium with alumina using co-precipitation technique, the addition of gemini surfactant showed a good impact on CO2 capture performance as an increase in CO2 sorption capacity was observed. However, sintering effect was still not yet be resolved with the addition of gemini surfactant as CO2 sorption capacity decreased upon multiple cycles of CO2 capture.